KONSTRUKSI SOSIAL KEKERASAN SEKSUAL PADA ANAK DI PONDOK PESANTREN MANARUL HUDA KOTA BANDUNG - Ulfah Karimah Yamani; Wahyu Gunawan; Muhammad Fedryansyah (Jurnal Ilmiah Global Education, 2023)
Children are people who are very vulnerable to sexual violence. Sexual harassment can occur anywhere, including in institutions with strong religious foundations that uphold high moral standards. This study intends to examine how sexual violence against children is socially constructed at the Manarul Huda Islamic Boarding School, Bandung. To understand the social construction of sexual violence against minors in Islamic boarding schools, this study uses a qualitative methodology and case study techniques. The analytical tool used is Peter L. Berger's theory of Social Construction. As a result of research, this can be explained through 3 (three) stages, namely externalization where in this stage the child victim's understanding is limited to the basic concept of sexual violence, secondly the objectification of the meaning of the concept of sexual violence which is then understood by the child to feel confused and afraid of the perpetrator's actions accept. Third, internalization of what actions need to be taken when sexual violence occurs, during the 2016-2021 period sexual violence took place, from family abuse and child confessions, family victims who reported it to the police.